77.8k views
4 votes
Solve this equation 4log√x - log 3x =log x^2​

User Jsoverson
by
5.1k points

1 Answer

5 votes

Answer:


x = (1)/(3)

Explanation:

*Move terms to the left and set equal to zero:

4㏒(√x) - ㏒(3x) - ㏒(x²) = 0

*simplify each term:

㏒(x²) - ㏒(3x) - ㏒(x²)

㏒(x²÷x²) -㏒(3x)

㏒(x²÷x² / 3x)

*cancel common factor x²:

㏒(
(1)/(3x))

*rewrite to solve for x :

10⁰ =
(1)/(3x)

1 =
(1)/(3x)

1 · x =
(1)/(3x) · x

1x =
(1)/(3)

*that would be our answer, however, the convention is to exclude the "1" in front of variables so we are left with:

x =
(1)/(3)

User Oceanhug
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.